Genetic Study of Severe Prolonged Lymphopenia in Multiple Sclerosis Patients Treated With Dimethyl Fumarate - Sangurdekar, Dipen; Sun, Chao; McLaughlin, Helen; Ayling-Rouse, Katherine; Allaire, Normand E.; Penny, Michelle A.; Bronson, Paola G. (Frontiers in Genetics, 2019)
In delayed-release dimethyl fumarate (DMF)–treated patients, absolute lymphocyte count (ALC) often declines in the first year and stabilizes thereafter; early declines have been associated with development of severe prolonged lymphopenia (SPL). Prolonged moderate to severe lymphopenia is a risk factor for progressive multifocal leukoencephalopathy (PML). Aside from very rare cases of PML associated with DMF usage, there is no increased risk for other serious infections. It is unknown whether genetic predictors of SPL secondary to DMF treatment exist. We aimed to identify genetic predictors of reduced white blood cell (WBC) counts in DMF-treated multiple sclerosis (MS) patients. Genotyping (N=1,258) and blood transcriptional profiling (N=1,133) were performed on MS patients from DEFINE/CONFIRM. ALCs were categorized as: SPL, <500 cells/µl for ≥6 months; moderate prolonged lymphopenia (MPL), <800 cells/µl for ≥6 months, excluding SPL; mildly reduced lymphocytes, <910 cells/µl at any point, excluding SPL and MPL; no lymphopenia, ≥910 cells/µl. Genome-wide association, HLA, and cross-sectional gene expression studies were performed. No common variants, HLA alleles, or expression profiles clinically useful for predicting SPL or MPL were identified. There was no overlap between genetic peaks and genetic loci known to be associated with WBC. Gene expression profiles were not associated with lymphopenia status. A classification model including gene expression features was not more predictive of lymphopenia status than standard covariates. There were no genetic predictors of SPL (or MPL) secondary to DMF treatment. Our results support ALC monitoring during DMF treatment as the most effective way to identify patients at risk of SPL.